An Examination of College Persistence Factors for Students from Different Rural Communities: A Multilevel Analysis - Andrew Hudacs (Journal of Research in Rural Education, 2020)
Although some studies have explored the influence of academic achievement on rural students' college access and success, little research has analyzed the relationship between students of different types of rural communities and their persistence in postsecondary education. This study examined the likelihood of college-going students from three different types of rural communities to successfully transition into and persist at a four-year residential college. Specifically, multilevel logistic modeling was used to analyze the odds of students' persisting in college for at least two academic years based on whether they were from rural tourist communities, rural college communities, and other rural communities. The analysis controlled for a variety of student and high school factors. Findings revealed that student-level factors related to poverty and academic readiness have the greatest effects on college persistence, while the type of rural community has no significant influence.